Ring-Expansion Metathesis Polymerization under Confinement - Probst, Patrick; Lindemann, Moritz; Bruckner, Johanna R.; Atwi, Boshra; Wang, Dongren; Fischer, Felix Richard; Högler, Marc; Bauer, Matthias; Hansen, Niels; Dyballa, Michael; Buchmeiser, Michael R. (Journal of the American Chemical Society)
The cationic molybdenum alkylidyne N-heterocyclic carbene (NHC) complex [Mo(C-p-OMeC6H4)(OCMe(CF3)2)2 (IMes)][B(ArF4] (IMes = 1,3-dimesitylimidazol-2-ylidene) was selectively immobilized inside the pores of ordered mesoporous silica (OMS) with pore diameters of 66, 56, and 28 Å and used in the ring-expansion metathesis polymerization (REMP) of cyclic olefins to yield cyclic polymers. A strong confinement effect was observed for cis-cyclooctene (cCOE), 1,5-cyclooctadiene (COD), (+)-2,3-endo,exo-dicarbomethoxynorborn-5-ene ((+)-DCMNBE), and 2-methyl-2-phenylcycloprop-1-ene (MPCP), allowing for the synthesis of low-molecular-weight cyclic polymers even at a high monomer concentration. The exclusive formation of cyclic polymers was demonstrated by matrix-assisted laser desorption ionization time-of-flight (MALDI-TOF) mass spectrometry. Confinement also influences stereoselectivity, resulting in a pronounced increase in Z-selectivity and in an increased cis-syndiospecificity.

Chromophore Induced Effects in Iron(III) Complexes - Schmitz, Lennart; Argüello Cordero, Miguel A.; Al-Marri, Mohammed J.; Schoch, Roland; Egold, Hans; Neuba, Adam; Steube, Jakob; Bracht, Bastian Johannes; Bokareva, Olga S.; Lochbrunner, Stefan; Bauer, Matthias (Inorganic Chemistry)
In the search for noble metal free photocatalytic systems, iron is the dream candidate. To increase excited state lifetimes of iron complexes, the multichromophoric approach is promising, combining organic chromophores with photoactive iron complexes, potentially enabling a reservoir effect. We present a series of chromophore-functionalized complexes based on the parental FeIII complex [Fe(ImP)2][PF6] (HImP = 1,1′-(1,3-phenylene)bis(3-methyl-1-imidazole-2-ylidene)). The four organic chromophores benzene, naphthalene, anthracene, and pyrene are attached to the ImP-ligand in para-position to the coordination site to systematically investigate the influence of the steric demand and electronic properties of the chromophore on charge transfer lifetimes as well as photodynamics. A thorough ground state characterization was conducted in addition to investigations of the excited state dynamics by transient absorption spectroscopy and streak camera emission measurements. The conclusions drawn are supported by extensive DFT calculations. The emission coefficients could be significantly improved by the addition of chromophores. After excitation of the complexes with larger chromophores, coplanarization of the backbone and complex motif occurs to stabilize the formal charge. This results in population of a superligand state that exhibits a much faster radiationless relaxation to the ground state compared to the parent complex, hindering a reservoir effect.
Keywords: Photo

Low Temperature Emissive Cyclometalated Cobalt(III) Complexes - Krishna, Athul; Fritsch, Lorena; Steube, Jakob; Argüello Cordero, Miguel A.; Schoch, Roland; Neuba, Adam; Lochbrunner, Stefan; Bauer, Matthias (Inorganic Chemistry)
A series of CoIII complexes [Co(RImP)2][PF6], with HMeImP = 1,1′-(1,3-phenylene)bis(3-methyl-1-imidazole-2-ylidene)) and R = Me, Et, iPr, nBu, is presented in this work. The influence of the strong donor ligand on the ground and excited-state photophysical properties was investigated in the context of different alkyl substituents at the imidazole nitrogen. X-ray diffraction revealed no significant alterations of the structures and all differences in the series emerge from the electronic structures. These were probed via cyclic voltammetry and UV–vis spectroscopy, detailing the influence of the different alkyl substituents on the ground-state properties. All complexes are emissive at 77 K from a 3MC state, which exhibits lifetimes in the range of 1–5 ns at room temperature, depending on the alkyl substituent. Therefore, it is clearly shown that even small differences in the electronic structure have a large impact on the details of the excited state landscape. The observed behavior was rationalized by a detailed DFT analysis, which shows that the minimum-energy crossing point to the ground-state is located only slightly above the MC energy: Consequently, nonradiative decay to the ground state at room temperature is enabled, while at 77 K this path is prohibited, leading to low-temperature 3MC emission.
Keywords: Photo

Isostructural Series of a Cyclometalated Iron Complex in Three Oxidation States - Steube, Jakob; Fritsch, Lorena; Kruse, Ayla; Bokareva, Olga S.; Demeshko, Serhiy; Elgabarty, Hossam; Schoch, Roland; Alaraby, Mohammad; Egold, Hans; Bracht, Bastian Johannes; Schmitz, Lennart; Hohloch, Stephan; et al. (Inorganic Chemistry)
An isostructural series of FeII, FeIII, and Fe(IV)complexes [Fe(ImP)2]0/+/2+ utilizing the ImP 1,1′-(1,3-phenylene)-bis(3-methyl-1-imidazol-2-ylidene) ligand, combining N-heterocy-clic carbenes and cyclometalating functions, is presented. The strong donor motif stabilizes the high-valent Fe(IV) oxidation state yet keeps the FeII oxidation state accessible from the parent Fe(III)compound. Chemical oxidation of [Fe(ImP)2]+ yields stable [FeIV(ImP)2]2+. In contrast, [FeII(ImP)2]0, obtained by reduction,is highly sensitive toward oxygen. Exhaustive ground state characterization by single-crystal X-ray diffraction, 1H NMR,Mössbauer spectroscopy, temperature-dependent magnetic measurements, a combination of X-ray absorption near edge structureand valence-to-core, as well as core-to-core X-ray emission spectroscopy, complemented by detailed density functional theory (DFT) analysis, reveals that the three complexes[Fe(ImP)2]0/+/2+ can be unequivocally attributed to low-spin d6, d5, and d4 complexes. The excited state landscape of the Fe(II) and Fe(IV) complexes is characterized by short-lived 3MLCT and 3LMCT states, with lifetimes of 5.1 and 1.4 ps, respectively. In the FeII-compound, an energetically low-lying MC state leads to fast deactivation of the MLCT state. The distorted square-pyramidal state, where one carbene is dissociated, can not only relax into the ground state, but also into a singlet dissociated state. Its formation was investigated with time-dependent optical spectroscopy, while insights into its structure were gained by NMR spectroscopy.
Keywords: Photo

Ultrafast Two‐Color X‐Ray Emission Spectroscopy Reveals Excited State Landscape in a Base Metal Dyad - Nowakowski, Michał; Huber‐Gedert, Marina; Elgabarty, Hossam; Kalinko, Aleksandr; Kubicki, Jacek; Kertmen, Ahmet; Lindner, Natalia; Khakhulin, Dmitry; Lima, Frederico A.; Choi, Tae‐Kyu; Biednov, Mykola; Schmitz, Lennart; et al. (Advanced Science)
Effective photoinduced charge transfer makes molecular bimetallic assemblies attractive for applications as active light‐induced proton reduction systems. Developing competitive base metal dyads is mandatory for a more sustainable future. However, the electron transfer mechanisms from the photosensitizer to the proton reduction catalyst in base metal dyads remain so far unexplored. A Fe─Co dyad that exhibits photocatalytic H2 production activity is studied using femtosecond X‐ray emission spectroscopy, complemented by ultrafast optical spectroscopy and theoretical time‐dependent DFT calculations, to understand the electronic and structural dynamics after photoexcitation and during the subsequent charge transfer process from the Fe(II) photosensitizer to the cobaloxime catalyst. This novel approach enables the simultaneous measurement of the transient X‐ray emission at the iron and cobalt K‐edges in a two‐color experiment. With this methodology, the excited state dynamics are correlated to the electron transfer processes, and evidence of the Fe→Co electron transfer as an initial step of proton reduction activity is unraveled.
Keywords: Photo; Xray

Insights into the First Multi-Transition-Metal Containing Ruddlesden Popper-Type Cathode for all-solid-state Fluoride Ion Batteries - Vanita, Vanita; Waidha, Aamir Iqbal; Vasala, Sami; Puphal, Pascal; Schoch, Roland; Glatzel, Pieter; Bauer, Matthias; Clemens, Oliver (Journal of Materials Chemistry A)
Promising cathode materials for fluoride-ion batteries (FIBs) are 3d transition metal containing oxides with Ruddlesden-Popper-type structure. So far, multi-elemental compositions were not investigated, but could alternate electrochemical performance similar to what has been found for cathode materials for lithium-ion batteries. Within this study, we investigate RP type La2Ni0.75Co0.25O4.08 as an intercalation-based active cathode material for all-solid-state FIBs. We determine the structural changes of La2Ni0.75Co0.25O4.08 during fluoride intercalation / de-intercalation by ex-situ X-ray diffraction, which showed that F- insertion leads to transformation of the parent phase to three different phases. Changes in Ni and Co oxidation states and coordination environment were examined by X-ray absorption spectroscopy and magnetic measurements in order to understand the complex reaction behaviour of the phases in detail, showing that the two transition metals behave differently in the charging and discharging process. Under optimized operating conditions, a cycle life of 120 cycles at a critical cut-off capacity of 40 mAh g-1 against Pb/PbF2 was obtained, which is one of the highest observed for intercalation electrode materials in FIBs so far. The average Coulombic efficiencies ranged from 85% to 90%. Thus, La2Ni0.75Co0.25O4.08 could be a promising candidate for cycling-stable high-energy cathode materials for all-solid-state FIBs
Keywords: Xray

Hydrogen spillover through hydride transfer: the reaction of ZnO and ZrO2 with strong hydride donors - Benz, Michael; Bunjaku, Osman; Nowakowski, Michał; Allgaier, Alexander; Biswas, Indro; van Slageren, Joris; Bauer, Matthias; Estes, Deven P. (Catalysis Science & Technology)
Hydride donors such as DIBAL or CuH react with ZnO and ZrO2 via hydrogen spillover. This suggests that hydrogen spillover in catalysts based on these metal oxides may take place via initial hydride transfer and not via proton–electron transfer.
Keywords: Xray

Detection and Characterization of Hydride Ligands in Copper Complexes by Hard X‐ray Spectroscopy - Fritsch, Lorena; Rehsies, Pia; Barakat, Wael; Estes, Deven P.; Bauer, Matthias (Chemistry – A European Journal)
Transition metal complexes, particularly copper hydrides, play an important role in various catalytic processes and molecular inorganic chemistry. This study employs synchrotron hard X‐ray spectroscopy to gain insights into the geometric and electronic properties of copper hydrides as potential catalysts for CO2 hydrogenation. The potential of high energy resolution X‐ray absorption near‐edge structure (HERFD‐XANES) and valence‐to‐core X‐ray emission (VtC‐XES) is demonstrated with measurement on Stryker's reagent (Cu6H6) and [Cu3(μ3‐H)(dpmppe)2](PF6)2 (Cu3H), alongside a non‐hydride copper compound (Cu‐I). The XANES analysis reveals that coordination geometries strongly influence the spectra, providing only indirect details about hydride coordination. The VtC‐XES analysis exhibits a distinct signal around 8975 eV, offering a diagnostic tool to identify hydride ligands. Theoretical calculations support and extend these findings by comparing hydride‐containing complexes with their hydride‐free counterparts.
Keywords: Xray

New and Facile Preparation Method for Highly Active Iron Oxide Catalysts for CO Oxidation - Schlicher, Steffen; Schoch, Roland; Prinz, Nils; Zobel, Mirijam; Bauer, Matthias (Catalysts)
This work presents a new and facile route for the preparation of iron oxide-based catalysts supported on alumina, which enables the targeted synthesis of catalysts with an increased amount of isolated tetrahedrally coordinated iron centers compared to a conventional impregnation procedure, and therefore leads to an increase in activity for CO oxidation reaction. By a multi-step impregnation–calcination protocol, the catalysts were synthesized with iron loadings of between 1 and 10 wt%, and their catalytic activity was then compared with a 10 wt% loaded catalyst prepared by conventional single impregnation. With a loading of 8 wt%, the presented catalysts showed an improved catalytic activity regarding light-off and full conversion temperatures compared to this reference. Through the application of several analytical methods (PXRD, PDF, DRUVS, SEM, XAFS), the improved catalytic activity can be correlated with an increased amount of isolated iron centers and a significantly reduced fraction of agglomerates or particles.
Keywords: Catalysis

Electronic Structure and Excited-State Dynamics of the NIR-II Emissive Molybdenum(III) Analogue to the Molecular Ruby - Kitzmann, Winald R.; Hunger, David; Reponen, Antti-Pekka M.; Förster, Christoph; Schoch, Roland; Bauer, Matthias; Feldmann, Sascha; van Slageren, Joris; Heinze, Katja (Inorganic Chemistry)
Photoactive chromium(III) complexes saw a conceptual breakthrough with the discovery of the prototypical molecular ruby mer-[Cr(ddpd)2]3+ (ddpd = N,N′-dimethyl-N,N′-dipyridin-2-ylpyridine-2,6-diamine), which shows intense long-lived near-infrared (NIR) phosphorescence from metal-centered spin-flip states. In contrast to the numerous studies on chromium(III) photophysics, only 10 luminescent molybdenum(III) complexes have been reported so far. Here, we present the synthesis and characterization of mer-MoX3(ddpd) (1, X = Cl; 2, X = Br) and cisfac-[Mo(ddpd)2]3+ (cisfac-[3]3+), an isomeric heavy homologue of the prototypical molecular ruby. For cisfac-[3]3+, we found strong zero-field splitting using magnetic susceptibility measurements and electron paramagnetic resonance spectroscopy. Electronic spectra covering the spin-forbidden transitions show that the spin-flip states in mer-1, mer-2, and cisfac-[3]3+ are much lower in energy than those in comparable chromium(III) compounds. While all three complexes show weak spin-flip phosphorescence in NIR-II, the emission of cisfac-[3]3+ peaking at 1550 nm is particularly low in energy. Femtosecond transient absorption spectroscopy reveals a short excited-state lifetime of 1.4 ns, 6 orders of magnitude shorter than that of mer-[Cr(ddpd)2]3+. Using density functional theory and ab initio multireference calculations, we break down the reasons for this disparity and derive principles for the design of future stable photoactive molybdenum(III) complexes.
Keywords: Inorganic Chemistry; Physical and Theoretical Chemistry

Investigations of Ni-based methanation catalysts under dynamic conditions via hard X-ray spectroscopy - Strübbe, Sven
Im Rahmen dieser Dissertation wurden Katalysatoren, welche auf der thermischen Zersetzung von metallorganischen Gerüstverbindungen basieren, mittels Röntgenabsorptionsspektroskopie (XAS) und Röntgenemissionsspektroskopie (XES) untersucht. Durch diesen synthetischen Ansatz können hochdisperse Ni-basierte Katalysatoren eingebettet in einer Kohlenstoffmatrix gewonnen werden, welche für die Methanisierung von CO2 Einsatz finden. Diese sollen eine hohe Stabilität gegenüber Wasserstoffausfällen aufweisen, welche bedingt durch Wetterfluktuationen in der Gewinnung von grünem Wasserstoff auftreten. Um ein derartiges System gezielt gestalten zu können, ist ein detailliertes Verständnis zugrundeliegender chemischer Mechanismen und damit einhergehend elektronischer Strukturen der Katalysatorsysteme notwendig. Durch die detaillierte Analyse der Katalysator-Vorstufen mittels XAS konnte gezeigt werden, dass auch unter reduktiven Bedingungen in der thermischen Zersetzung Spuren von Ni(II) vorliegen und keine reine Nifcc-Struktur erreicht werden konnte. Eine detaillierte Auswertung der gleichen Präkatalysatoren mittels XES konnte durch eine neuartige Kombination von HERFD-XANES, theoretischer Berechnungen und VtC-XES einen eindeutigen Beweis für das Vorhandensein der gewünschten Kohlenstoffmatrix sowie Spuren von NiO im Präkatalysator liefern, welche sich vorteilhaft auf die spätere Aktivität im finalen Katalysator auswirken. Abschließend konnte mittels einer in-situ Untersuchung der Temperaturbereich, in dem sich die aktive Katalysatorspezies ausbildet, auf 80 bis 200 C eingegrenzt werden. Schließlich konnte ein eindeutiger Zusammenhang zwischen dem Verlust einer stabilisierenden Kohlenstoffschicht und einem Rückgang der Aktivität belegt werden.

Macrocyclization of Dienes under Confinement with Cationic Tungsten Imido/Oxo Alkylidene N‐Heterocyclic Carbene Complexes - Ziegler, Felix; Bruckner, Johanna R.; Nowakowski, Michał; Bauer, Matthias; Probst, Patrick; Atwi, Boshra; Buchmeiser, Michael R. (ChemCatChem)
Macrocyclization reactions are still challenging due to competing oligomerization, which requires the use of small substrate concentrations. Here, the cationic tungsten imido and tungsten oxo alkylidene N-heterocyclic carbene complexes [[W(N-2,6-Cl2-C6H3)(CHCMe2Ph(OC6F5)(pivalonitrile)(IMes)+ B(ArF)4−] (W1) and [W(O)(CHCMe2Ph(OCMe(CF3)2)(IMes)(CH3CN)+ B(ArF)4−] (W2) (IMes=1,3-dimesitylimidazol-2-ylidene; B(ArF)4−=tetrakis(3,5-bis(trifluoromethyl)phenyl borate) have been immobilized inside the pores of ordered mesoporous silica (OMS) with pore diameters of 3.3 and 6.8 nm, respectively, using a pore-selective immobilization protocol. X-ray absorption spectroscopy of W1@OMS showed that even though the catalyst structure is contracted due to confinement by the mesopores, both the oxidation state and structure of the catalyst stayed intact upon immobilization. Catalytic testing with four differently sized α,ω-dienes revealed a dramatically increased macrocyclization (MC) and Z-selectivity of the supported catalysts compared to the homogenous progenitors, allowing high substrate concentrations of 25 mM. With the supported complexes, a maximum increase in MC-selectivity from 27 to 81 % and in Z-selectivity from 17 to 34 % was achieved. In general, smaller mesopores exhibited a stronger confinement effect. A comparison of the two supported tungsten-based catalysts showed that W1@OMS possesses a higher MC-selectivity, while W2@OMS exhibits a higher Z-selectivity which can be rationalized by the structures of the catalysts.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Catalysis

Janus-type emission from a cyclometalated iron(iii) complex - Steube, Jakob; Kruse, Ayla; Bokareva, Olga S.; Reuter, Thomas; Demeshko, Serhiy; Schoch, Roland; Argüello Cordero, Miguel A.; Krishna, Athul; Hohloch, Stephan; Meyer, Franc; Heinze, Katja; Kühn, Oliver; et al. (Nature Chemistry)
Abstract Although iron is a dream candidate to substitute noble metals in photoactive complexes, realization of emissive and photoactive iron compounds is demanding due to the fast deactivation of their charge-transfer states. Emissive iron compounds are scarce and dual emission has not been observed before. Here we report the Fe III complex [Fe(ImP) 2 ][PF 6 ] (HImP = 1,1′-(1,3-phenylene)bis(3-methyl-1-imidazol-2-ylidene)), showing a Janus-type dual emission from ligand-to-metal charge transfer (LMCT)- and metal-to-ligand charge transfer (MLCT)-dominated states. This behaviour is achieved by a ligand design that combines four N -heterocyclic carbenes with two cyclometalating aryl units. The low-lying π * levels of the cyclometalating units lead to energetically accessible MLCT states that cannot evolve into LMCT states. With a lifetime of 4.6 ns, the strongly reducing and oxidizing MLCT-dominated state can initiate electron transfer reactions, which could constitute a basis for future applications of iron in photoredox catalysis.
Keywords: General Chemical Engineering; General Chemistry

Understanding the Redox Mechanism of Sulfurized Poly(acrylonitrile) as Highly Rate and Cycle Stable Cathode Material for Sodium-Sulfur Batteries - Kappler, Julian; Tonbul, Güldeniz; Schoch, Roland; Murugan, Saravanakumar; Nowakowski, Michał; Lange, Pia Lena; Klostermann, Sina Vanessa; Bauer, Matthias; Schleid, Thomas; Kästner, Johannes; Buchmeiser, Michael Rudolf (Journal of The Electrochemical Society)
Room temperature sodium-sulfur (RT Na-S) batteries are considered potential candidates for stationary power storage applications due to their low cost, broad active material availability and low toxicity. Challenges, such as high volume expansion of the S-cathode upon discharge, low electronic conductivity of S as active material and herewith limited rate capability as well as the shuttling of polysulfides (PSs) as intermediates often impede the cycle stability and practical application of Na-S batteries. Sulfurized poly(acrylonitrile) (SPAN) inherently inhibits the shuttling of PSs and shows compatibility with carbonate-based electrolytes, however, its exact redox mechanism remained unclear to date. Herein, we implement a commercially available and simple electrolyte into the Na-SPAN cell chemistry and demonstrate its high rate and cycle stability. Through the application of in situ techniques utilizing electronic impedance spectroscopy (EIS) and X-ray absorption spectroscopy (XAS) at different depths of charge and discharge, an insight into SPAN’s redox chemistry is obtained.
Keywords: Materials Chemistry; Electrochemistry; Surfaces; Coatings and Films; Condensed Matter Physics; Renewable Energy; Sustainability and the Environment; Electronic; Optical and Magnetic Materials

Characterization of Na-S Battery System Using X-ray Absorption Spectroscopy - Tonbul, Güldeniz; Kappler, Julian; Murugan, Saravanakumar; Schoch, Roland; Nowakowski, Michal; Lange, Pia; Bauer, Matthias; Buchmeiser, Michael R.

Ultrafast two-colour X-ray emission spectroscopy reveals excited state landscape in a base metal dyad - Nowakowski, Michał; Huber-Gedert, Marina; Elgabarty, Hossam; Kubicki, Jacek; Kertem, Ahmet; Lindner, Natalia; Khakhulin, Dimitry; Lima, Frederico Alves; Choi, Tae-Kyu; Biednov, Mykola; Piergies, Natalia; Zalden, Peter; et al. (arxiv)
Effective photoinduced charge transfer makes molecular bimetallic assemblies attractive for applications as active light induced proton reduction systems. For a more sustainable future, development of competitive base metal dyads is mandatory. However, the electron transfer mechanisms from the photosensitizer to the proton reduction catalyst in base metal dyads remain so far unexplored. We study a Fe-Co dyad that exhibits photocatalytic H2 production activity using femtosecond X-ray emission spectroscopy, complemented by ultrafast optical spectroscopy and theoretical time-dependent DFT calculations, to understand the electronic and structural dynamics after photoexcitation and during the subsequent charge transfer process from the FeII photosensitizer to the cobaloxime catalyst. Using this novel approach, the simultaneous measurement of the transient Kalpha X-ray emission at the iron and cobalt K-edges in a two-colour experiment is enabled making it possible to correlate the excited state dynamics to the electron transfer processes. The methodology, therefore, provides a clear and direct spectroscopic evidence of the Fe->Co electron transfer responsible for the proton reduction activity.

Tethering chiral Rh diene complexes inside mesoporous solids: experimental and theoretical study of substituent, pore and linker effects on asymmetric catalysis - Kirchhof, Manuel; Gugeler, Katrin; Beurer, Ann-Katrin; Fischer, Felix Richard; Batman, Derman; Bauch, Soeren M.; Kolin, Sofia; Nicholas, Elliot; Schoch, Roland; Vogler, Charlotte; Kousik, Shravan R.; Zens, Anna; et al. (Catalysis Science Technology)
Improved enantioselectivity in the 1,2-addition was observed for chiral Rh norbornadiene catalysts immobilized on ordered mesoporous silica with small pores. Confinement effects were rationalized by experimental and computational studies.
Keywords: Catalysis

Chemical and photophysical properties of amine functionalized bis‐NHC‐pyridine‐Ru(II) complexes - Fritsch, Lorena; Vukadinovic, Yannik; Lang, Moritz; Naumann, Robert; Bertrams, Maria-Sophie; Kruse, Ayla; Schoch, Roland; Müller, Patrick; Neuba, Adam; Dierks, Philipp; Lochbrunner, Stefan; Kerzig, Christoph; et al. (ChemPhotoChem)
The effects of backbone amine functionalization in three new homoleptic C^N^C type ruthenium(II) complexes bearing a tridentate bis‐imidazole‐2‐ylidene pyridine ligand framework are characterized and studied by single crystal diffraction, electrochemistry, optical spectroscopy and transient absorption spectroscopy in combination with ab initio DFT calculations. Functionalization by dimethylamine groups in 4‐position of the pyridine backbone significantly influences the properties of the complexes as revealed by comparison with the unfunctionalized references. As a result of the amine functionalization, a higher molar absorption coefficient of the MLCT bands, a decreased photoluminescence quantum yield at room temperature together with a shortened excited state lifetime but an improved photostability is observed. Introduction of electron donating and withdrawing groups at the NHC unit modifies the electronic and optical properties, such as the oxidation potential, absorption and emission properties, and the lifetimes of the excited states.
Keywords: Photo

High resolution off resonant spectroscopy as a probe of the oxidation state - Nowakowski, Michał; Kalinko, Aleksandr; Szlachetko, Jakub; Fanselow, Rafał; Bauer, Matthias (Journal of Analytical Atomic Spectrometry)
Currently, chemistry and physics are strongly dependent on the concept of the oxidation state. While the formal oxidation state is easily evaluated, the real physical oxidation state value is often difficult to determine and significantly varies from the formal values. Determination of the ionization threshold in X-ray absorption spectroscopy (XANES) relies on the absorption edge position and sometimes poses limitations, mainly due to the edge resonances. Moreover, the lower energy states can be probed only within x-soft or XUV photons providing only surface state information of probed materials. Here, we employ high energy resolution off-resonant spectroscopy to determine both 1s and 3p binding energies of Fe-based materials and therefore correlate to their physical oxidation state. The results are compared to the ones obtained with classical X-ray absorption, X-ray emission, and photoelectron spectroscopies. The observed differences in binding energies are discussed in a frame of initial and final state interactions with the atom's electronic configurations. The presented methodology is discussed towards potential use to single-shot experiments and application at X-ray free-electron lasers. Alternatively, core level X-ray emission spectroscopy can be used, but the emission line positions are strongly affected by spin-orbit interaction. However, due to the energy transfer from the photon to the excited core electron, the same information as in XANES is probed in high energy resolution off-resonant spectroscopy (HEROS). Based on the Kramers–Heisenberg theory, we propose a new approach for ionization threshold determination which is free of the limitations encountered in XANES-based determination of the core state energy. Namely, the value of core state energy can be determined analytically using a few HEROS spectra recorded with significantly higher spectral resolution. This approach provides a basis for the universal physical oxidation state determination method.
Keywords: Spectroscopy; Analytical Chemistry

Digitization in Catalysis Research: Towards a Holistic Description of a Ni/Al2O3 Reference Catalyst for CO2 Methanation - Weber, Sebastian; Zimmermann, Ronny T.; Bremer, Jens; Abel, Ken L.; Poppitz, David; Prinz, Nils; Ilsemann, Jan; Wendholt, Sven; Yang, Qingxin; Pashminehazar, Reihaneh; Monaco, Federico; Cloetens, Peter; et al. (ChemCatChem)
Increasing the metal-to-ligand charge transfer (MLCT) excited state lifetime of polypyridine iron(II) complexes can be achieved by lowering the ligand's π* orbital energy and by increasing the ligand field splitting. In the homo- and heteroleptic complexes [Fe(cpmp)2]2+ (12+) and [Fe(cpmp)(ddpd)]2+ (22+) with the tridentate ligands 6,2’’-carboxypyridyl-2,2’-methylamine-pyridyl-pyridine (cpmp) and N,N’-dimethyl-N,N’-di-pyridin-2-ylpyridine-2,6-diamine (ddpd) two or one dipyridyl ketone moieties provide low energy π* acceptor orbitals. A good metal-ligand orbital overlap to increase the ligand field splitting is achieved by optimizing the octahedricity through CO and NMe units between the coordinating pyridines which enable the formation of six-membered chelate rings. The push-pull ligand cpmp provides intra-ligand and ligand-to-ligand charge transfer (ILCT, LL'CT) excited states in addition to MLCT excited states. Ground and excited state properties of 12+ and 22+ were accessed by X-ray diffraction analyses, resonance Raman spectroscopy, (spectro)electrochemistry, EPR spectroscopy, X-ray emission spectroscopy, static and time-resolved IR and UV/Vis/NIR absorption spectroscopy as well as quantum chemical calculations.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Catalysis